1987
DOI: 10.4141/cjas87-003
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Luteum Activity and Prostaglandin Levels After Parturition in Cows With Retained Fetal Membranes

Abstract: MATT'N, P., ADELAK''w, V. eNo Duroun, J. lgg7. Corpus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…For spontaneous retained placenta, several studies have observed no significant difference in oestrogen concentrations from normally calving cows (Matton and others 1979, Elecko and others 1982, Inaba and others 1986). Agthe and Kolm (1975), however, found that cows with retained placenta had a marked increase in oestrogen concentration within 12 hours post partum, whereas there was little change in its mean concentration in normal cows.…”
Section: Aetiology Of Retained Placentamentioning
confidence: 98%
“…For spontaneous retained placenta, several studies have observed no significant difference in oestrogen concentrations from normally calving cows (Matton and others 1979, Elecko and others 1982, Inaba and others 1986). Agthe and Kolm (1975), however, found that cows with retained placenta had a marked increase in oestrogen concentration within 12 hours post partum, whereas there was little change in its mean concentration in normal cows.…”
Section: Aetiology Of Retained Placentamentioning
confidence: 98%
“…Lamming et • al. 1981, Lindell et al 1982a, Thatcher et al 1982, Larsson et al 1984, Matton et al 1987, Eldon 1991, Kindahl et al 1992 suggests that the progesterone and/or PGF 2 a profiles provide basic information on the pathophysiological changes prior to or after the reestablishment of the oestrous cycle. Moreover, the bovine uterus and placenta are considered to be the main source of prostaglandin during early pp (Lindell et al l 982b, Guilbault et al 1984, Kankofer et al l 994).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, retained foetal membranes and the subsequent development of endometritis have been associated with a disturbed synthesis and metabolism of PGF 2 a in the uterus (Lindell et al I 982a, Thatcher et al l 982, Bosu et al l 984, Chassagne & Barnouin 1992), reflecting the degree of endometrial damage or repair , Fredriksson et al 1988. In cows with retained foetal membranes, a prolonged duration of high plasma levels of the main PGF 2 a metabolite ( 15-ketodihydro-PGF 2 a) was observed (Lindell et al l 982a, Fredriksson et al 1985, Matton et al 1987. From these studies it can be concluded that the duration and possibly the magnitude of the release of PGF ia are positively correlated to the time required for completion of uterine involution, and cyclical ovarian activity does not resume until the concentration of the PGF 2 a metabolite is again at a basal level.…”
Section: Introductionmentioning
confidence: 99%
“…Gambarini (1989) determined concentration of PGEM and PGFM in peripheral blood and reported lower concentration of PGFM in cows with retained placenta compared with cows without retained placenta. In contrast to those results, some authors (Bosu et al, 1984;Peter & Bosu, 1987;Matton et al, 1987) found that cows with retained placental membranes had higher concentrations of PGFM in peripheral blood than cows with undisturbed separation. Bosu et al (1984) observed an increase in PGFM concentration in peripheral blood starting about 6 days before parturition in cows with retained placental membranes, whereas in animals withoutretained placental membranes, the increase occurred later, about 48 hours before delivery.…”
Section: Eicosanoids and The Release Of The Placental Membranesmentioning
confidence: 64%